(untitled) (Scientific journal of the Fergana State University, 2024)
The paper discusses the emergence, development and progress of affixoids, which are considered a morphological form. Affixoids such as -sher, -tai, -khan, -zhan, -niso, -zoda, -khodzha, -bibi, -tora, -oy, -mirza, -bek, -bobo, -poshsha, -shukur, -bota, -kozi, -kul have been analysed and the imbalances arising in them have been scientifically substantiated. The place of affixoids in the language system, their meanings are shown on the example of form-forming affixoid.